Recovery kinetics of oxygen uptake following severe-intensity exercise in runners - Perrey, S.; Candau, R.; Borrani, F.; Millet, G. Y.; Rouillon, J. D. (The Journal of Sports Medicine and Physical Fitness, 2002)
BACKGROUND: This investigation sought to characterise the oxygen uptake (VO2) off-transient kinetics from severe exercise and to clarify discrepancies between on- and off-transient kinetics for VO2 seen in humans. METHODS: Eleven competitive endurance athletes underwent treadmill running until exhaustion at work-rates corresponding to the speed that elicited ~95% of maximal VO2. Gas exchange variables were determined breath-by-breath. Computerised non-linear regression techniques were used to fit the VO2 on- and off-transient kinetics. A 3-exponential model described the VO2 on-transient. VO2 off-transient was analysed to each response time course using 3 different models: a single-exponential model for the entire period and 2 3-exponential models where exponential terms starting either together after a common time delay or after independent time delays. RESULTS: Both 3-exponential models provided an excellent fit (r2>0.90) to the off-transient data. Compared with on-transient, VO2 off-transient kinetics was associated with a slower primary phase (time constant: 16+/-4 vs 39+/-13 sec, p<0.01) but was similar both in time delay and amplitude. CONCLUSIONS: These data indicate that there is no general symmetry between the exercise and recovery kinetics for VO2 because the response of the primary phase of VO2 off-transient resolves to a greater time constant, reflecting altered tissue metabolism. However, the mechanism(s) for the slow component is slow both in developing and to recover within the severe exercise domain.